1989
DOI: 10.1210/endo-125-4-1805
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Marrow-Derived Stromal Cell Lines MC3T3-G2/PA6 and ST2 Support Osteoclast-Like Cell Differentiation in Cocultures with Mouse Spleen Cells

Abstract: After our previous report that osteoclast-like multinucleated cells (MNCs) were formed in response to 1 alpha,25-dihydroxyvitamin D3 [1 alpha,25-(OH)2D3] in cocultures of mouse spleen cells and osteoblast-rich populations freshly isolated from fetal mouse calvariae, we examined whether such primary osteoblast-like cells can be replaced by established cell lines in inducing osteoclast-like cell formation. We first used two clonal cell lines simultaneously established from newborn mouse calvariae. One was the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
266
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(280 citation statements)
references
References 29 publications
11
266
1
2
Order By: Relevance
“…1,25-(OH) 2 VitD 3 is well known to effectively induce osteoclastogenesis in cocultures of mouse spleen cells and osteoblast-rich populations (Udagawa et al, 1989) and to increase RANKL expression and to decrease OPG expression (Horwood et al, 1998;Murakami et al, 1998;. Consistent with the previous reports, 1,25-(OH) 2 VitD 3 upregulated RANKL expression and downregulated OPG expression in mouse osteoblastic cells ( Figure 1B) and increased RANKL/OPG ratio upto~10 folds.…”
Section: Resultssupporting
confidence: 86%
“…1,25-(OH) 2 VitD 3 is well known to effectively induce osteoclastogenesis in cocultures of mouse spleen cells and osteoblast-rich populations (Udagawa et al, 1989) and to increase RANKL expression and to decrease OPG expression (Horwood et al, 1998;Murakami et al, 1998;. Consistent with the previous reports, 1,25-(OH) 2 VitD 3 upregulated RANKL expression and downregulated OPG expression in mouse osteoblastic cells ( Figure 1B) and increased RANKL/OPG ratio upto~10 folds.…”
Section: Resultssupporting
confidence: 86%
“…For example, it has been shown that Wnt10b-but not Wnt3a-RNA is present at a relatively high level in human mesenchymal precursor cells (27) and preadipocytes (41), and that Wnt10b RNA levels fall quite dramatically in these cell types following addition of adipocytogenic mixtures (43). Conversely, enforced Wnt10b expression in ST2 marrow-derived stromal cells (44) and 3T3-L1 preadipocytes suppresses adipocyte differentiation and lowers Pparγ RNA, even before adipogenesis is induced (41,43). Moreover, high-level Wnt10b expression in transgenic mice reduces both Pparγ expression and WAT development but not adipocyte size (45).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts or stromal cells express RANKL and M-CSF on the surface of cell membranes. A co-culture system of spleen cells with osteoblasts or bone marrow stromal cells has been established to produce osteoclasts (Takahashi et al 1988a, Udagawa et al 1989. RAW264·7 cells express M-CSF continuously, and thus can be clearly differentiated from osteoclast-like cells in the presence of sRANKL alone (Hsu et al 1999).…”
Section: Discussionmentioning
confidence: 99%